Subordinasi Perempuan dalam Budaya Patriarki Pada Film Kim Jiyoung, Born 1982 (2019) - Fara Syifa Amalia; Sulyana Dadan; Arizal Mutahir (Prodi Ilmu Komunikasi Universitas Putera Batam, 2026)
Womens subordination remains a form of gender inequality’s that is structural in nature and deeply rooted in patriarchal culture. This form of subordination occurs not only in everyday social life but is also represented through various media, including film. The film Kim Jiyoung, Born 1982 (2019) portrays the life experiences of South Korean women who face gender inequality across different spheres of life. This study aims to analyze how women’s subordination within patriarchal culture is represented through scenes and narratives in the film. The research employs a qualitative method using Charles Sanders Peirce’s semiotic approach. The research data consist of scenes, dialogues, and visual elements in the film, which are analyzed using the concepts of representamen, object, and interpretant. The analysis is further reinforced by Sylvia Walby’s theory of patriarchy to identify structural forms of women’s subordination and Stuart Hall’s theory of representation to understand the process of meaning construction in media. The findings reveal that women’s subordination is systematically represented in the domestic sphere, education, employment, and public space. Women are portrayed as experiencing role limitations, domestication, unequal access to opportunities, and marginalization in decision-making processes. These representations illustrate how patriarchal ideology operates subtly through social norms, power relations, and cultural practices that are normalized within society. This study concludes that Kim Jiyoung, Born 1982 functions not only as a reflection of social reality but also as a medium that constructs, reinforces, and critiques patriarchal structures that position women in subordinate roles within social life.